1,3-Diphenylisobenzofuran: a Model Chromophore for Singlet Fission - Johnson, Justin C; Michl, Josef (Topics in current chemistry, 2017)
In this review we first provide an introductory description of the singlet fission phenomenon and then describe the ground and electronically excited states of the parent 1,3-diphenylisobenzofuran chromophore (1) and about a dozen of its derivatives. A discussion of singlet fission in thin polycrystalline layers of these materials follows. The highest quantum yield of triplet formation by singlet fission, 200% at 80 K, is found in one of the two known crystal modification of the parent. In the other modification and in many derivatives, excimer formation competes successfully and triplet yields are low. A description of solution photophysics of covalent dimers is described in the next section. Triplet yields are very low, but interesting phenomena are uncovered. One is an observation of a separated-charges (charge-transfer) intermediate in highly polar solvents. The other is an observation of excitation isomerism in both singlet and triplet states, where in one isomer the excitation is delocalized over both halves of the covalent dimer, whereas in the other it is localized on one of the halves. In the last section we present the operation of a simple device illustrating the use of triplets generated by singlet fission for charge separation.
Keywords: benzofurany; chemické modely; Models, Chemical; Solvents; Benzofurans; Quantum Theory; rozpouštědla; elektrony; kvantová teorie; Electrons